Two distinct shortening events during late Archean orogeny in the west-central Slave Province, Northwest Territories, Canada - Relf, C. (Canadian Journal of Earth Sciences, 1992)
Late Archean structures in the west-central part of the Slave Province formed during two separate orogenic events. Evidence for early folding and thrusting in an accretionary prism is confined to a narrow belt along the east margin of an older microcontinent (the Anton terrane) in the west part of the province. Structures related to this event are overprinted by regional low-pressure metamorphism. Subsequent shortening occurred in a continental-arc setting in which folding and faulting was accompanied by calc-alkaline magmatism and regional low-pressure metamorphism. Although the entire region was affected, the bulk of shortening during the second orogenic event occurred east of the early fold and thrust belt. The first orogenic event produced a suture zone between old continental crust to the west and juvenile rocks to the east, and during the second orogenic event rocks on either sides of the suture were tectonically underplated and intruded.